Association between lifestyle inflammation score and quality of life according to depressive symptom status: a cross-sectional study in the Republic of Korea - Jaegeun Cho; Eunvin Kang; Young-Joo Won (Osong Public Health and Research Perspectives, 2026)
Objectives: This study examined the association between lifestyle inflammation score (LIS) and health-related quality of life, assessed using the EuroQol-5 Dimensions (EQ-5D) index, among adults in the Republic of Korea. It also evaluated whether depressive symptoms moderated this association.Methods: Data from the 2024 Community Health Survey were analyzed, and 231,386 adults were included. LIS was calculated by integrating smoking, alcohol consumption, physical activity, and body mass index. The dependent variable, quality of life, was assessed using the EQ-5D index. Depressive symptoms, the moderator variable, were assessed using the Patient Health Questionnaire-9, with a score of ≥10 indicating depressive symptoms. Data were analyzed using complex-sample multivariable linear regression to examine interaction effects according to depressive symptom status, followed by simple-slope analyses.Results: After adjustment for demographic and health-related variables, LIS was significantly and negatively associated with the EQ-5D index (β=–0.0069, p